Developing long-term risk & resilience management strategies for physical asset and critical infrastructure projects - Helmrich, A.; Gerber, B.; Gall, M.; Horton, P.; El Asmar, M.; Sailor, D.; Neveu, M.; El Kassis, R.; Sanboskani, H.; Vogel, A.; Yu, Y.; White, D. (Frontiers in Built Environment, 2025)
To account for increasing complexity and uncertainty in environmental, social, and technological systems, organizations that manage risk and vulnerability while maintaining large physical asset or infrastructure projects must identify, inventory, and anticipate trade-offs across multiple drivers of change. This article describes an integrated and inclusive process to develop a capabilities-based planning (CBP) framework to inform decision-making for future investments, centering hazard risk reduction and operational resilience. The proposed CBP framework demonstrates an approach to addressing context-specific complexity and uncertainty in decision-making by assessing short and long-term risk within a defined analytic focus. A case study of application is provided, examining the impacts of climate, resource, population, urbanization, and technology drivers on foreign assets for the U.S. Department of State Bureau of Overseas Buildings Operations in Kolkata, India. The process broadly applies to organizations with projects of physical assets and critical infrastructure, which balance tensions in decision-making across multiple objectives in diverse contexts.